Chemical cuticular signature of leafcutter ant Atta sexdens (Hymenoptera, Formicidae) worker subcastes - Valadares,Lohan (2016)
ABSTRACT In leafcutter ants the division of labour is associated to worker size variation clustered in four subcastes. In this work we used Atta sexdens Forel (1908) as a model to test the hypothesis that each subcaste expresses its own chemical signature comprised of cuticular lipids. To assess it, we extracted epicuticular compounds by using nonpolar solvent hexane and analysed the samples in a combined Gas Chromatography-Mass Spectrometer (GC-MS). We found 24 hydrocarbons with carbon chains ranging from 19 to 39 atoms most of them classified as linear and branched alkanes. No compound occurred in the cuticle of specific worker subcaste, however, the relative proportion pattern varied greatly among them. Our results suggest that although subcastes have similar chemical signatures, significant differences in their relative proportions may play an important role between nestmate and group identification.